Analysis Of Service Quality On Satisfaction Customers On Telkomsel Cards With Confirmatory Factor Analysis Method - Rahmi, Ruslina (SEAN Institute, 2024)
PT. Cellular Telecommunications or in short Telkomsel is a subsidiary of Telkom Indonesia which operates in the telecommunications sector for individual consumers (until 2023 it only deals in cellular telecommunications). The more mobile companies develop, the tighter the competition between companies becomes, so there is a need for an analysis that discusses the factors that have the most influence on the company's development, one of which is by looking at customer satisfaction factors. The progress of a company is influenced by the company's ability to serve its customers. In terms of services offered by the company, it is necessary to pay attention that the quality standards offered to customers must exceed customer expectations, so that customer satisfaction can be easily achieved by the Company. In statistics, there are several factor analysis methods, including Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) . The confirmatory method is a multifarious method that can be used to test or confirm a hypothesized model. This method is a measurement method in multivariate equation modeling. This model is more flexible compared to the general classical approach. From the results of research conducted using two-stage confirmatory factor analysis, several conclusions can be put forward that the indicators that influence service quality on customer satisfaction on Telkomsel cards using the Confirmatory Factor Analysis (CFA) method are the total contribution made by service quality to customer satisfaction at PT Telkomsel is equal to 0.824. This shows that the service quality dimension which measures the customer satisfaction variable can explain this influence by 82.4%.